'There is a dependent patient in our home': designing and disseminating a family caregiving program through YouTube. Issue 2 (June 2016) - Abu Kamel, Andaleeb
Abstract : Background: Family members play a major role in providing care for older people and long-term dependent patients, especially in developing countries where there is a lack of specialized nursing homes and specialized home-visiting programs. Family members are rarely provided with sufficient information or training to provide home care for their dependent relatives. There are inadequate home caregiving educational resources directed to Arabic-speaking caregivers, either in written or in audiovisual presentations. Objectives: The aims of the present study were (i) to present the process of designing a caregiving educational program entitled 'there is a dependent patient in our home', with an intention to be culturally and linguistically appropriate for a specific Arab-speaking population, and (ii) to present the experience of disseminating the program through YouTube, to be accessible for a wide range of caregivers. Materials and methods: The program was a product of a process involving seven phases, starting with a review of the literature and ending with disseminating 17 short 'caregiving' videos on YouTube, the most popular video-sharing website. The program presented necessary skills, instructions, and information that enabled caregivers to provide safe and competent daily caring activities for their functionally dependent relative or older adults at home. Results: The program was registered in the Jordan National Library. After 2 months of broadcasting it on YouTube, the number of views exceeded 6800. Many constructive comments were received from caregivers. Language, simplicity, and attractiveness of the program were judged as the areas of satisfaction by the viewers, whereas lack of a few topics such as verbal communication with patients and dealing with daily caregivers' burden and stressors were the main reasons of dissatisfaction. Conclusion: This program was an endeavor to provide the Arabic library with a home caregiving resource. Adequate advertisement of the program would encourage health providers to search for and use the currently available social media as means of delivering educational services to family caregivers.